2015
DOI: 10.4238/2015.september.9.9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of heterosis in interspecific hybrids of Argopecten purpuratus x A. irradians irradians

Abstract: ABSTRACT. Argopecten purpuratus and Argopecten irradians irradians hybridization was successfully performed and the hybrid offspring displayed apparent heterosis in growth traits. To better understand the genetic basis of heterosis, the genomic composition and genetic variation of the hybrids were analyzed with amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) markers. Seven of eight universal SSR primers displayed polymorphism in the hybrids and their parental groups, and hybrids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Currently, in the literature the time scale of nutritional-intervention studies in CKD patients is variable and in most of them, this comprises between one and twenty-four weeks. For this reason, the choice of 9 weeks of treatment with EVOO and of 2 months of wash-out period has been driven by the mean time of treatment present in the literature [11,13,19,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in the literature the time scale of nutritional-intervention studies in CKD patients is variable and in most of them, this comprises between one and twenty-four weeks. For this reason, the choice of 9 weeks of treatment with EVOO and of 2 months of wash-out period has been driven by the mean time of treatment present in the literature [11,13,19,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al [51] suggested that hybridisation between two populations increased genetic diversity indicators such as N a , H e , and H o in oysters and significantly reduced F is . Hu et al [52] suggested that intraspecific hybridisation can cause recombination of existing genes, which is an important way to increase biodiversity. However, genetic pollution is indeed a noteworthy problem, which reminds us that we cannot cross randomly, but must develop appropriate crossbreeding strategies to avoid genetic pollution.…”
Section: Genetic Diversity Of Microsatellite Loci and Cultured Popula...mentioning
confidence: 99%